Optimalisasi Peran Kader PIK-R: Transformasi Pengetahuan TRIAD KRR melalui Program Edukasi Kesehatan - Sheilia Handi Dwi Fadellia Maharani Putri; Nur Azizah Indriastuti (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
The three critical risk factors for adolescent reproductive health (TRIAD KRR) is an important issue that requires more attention. PIK-R staff are agents of change and act as partners who can influence young people themselves. Therefore, there is a need to improve staff knowledge about the TRIAD KRR by providing reproductive health education as a key strategy in efforts to improve PIK-R staff knowledge about the TRIAD KRR. This study aims to analyze the impact of health education on the knowledge level of PIK-R program staff about this triad. The study used a quasi-experimental design with a single group and pre- and post-tests. The sample consisted of 15 PIK-R program staff selected using a large-scale sampling method. The statistical analysis in this study was based on the Wilcoxon Signed-Rank test. The results showed a statistically significant difference in the knowledge level of the participants before receiving the health education program, with 10 participants (66.7%) having a good level of knowledge and 5 participants (33.3%) having a sufficient level of knowledge. After the program, 12 participants (80%) demonstrated a good level of knowledge, while 3 participants (20%) demonstrated a sufficient level of knowledge. Statistical analyses showed a statistically significant difference (p = 0.001, p < 0.05) between the level of knowledge before and after the health education program on the KRR TRIAD model. Therefore, it can be assumed that the health education had a significant impact on the knowledge of the participants in the PIK-R program on the TRIAD KRR model